Gold nanorod embedded novel 3D graphene nanocomposite for selective bio-capture in rapid detection of Mycobacterium tuberculosis - Perumal, V. (Elsevier Ltd, 2018)
Tuberculosis (TB) is a chronic and infectious airborne disease which requires a diagnosing system with high sensitivity and specificity. However, the traditional gold standard method for TB detection remains unreliable with low specificity and sensitivity. Nanostructured composite materials coupled with impedimetric sensing utilised in this study offered a feasible solution. Herein, novel gold (Au) nanorods were synthesized on 3D graphene grown by chemical vapour deposition. The irregularly spaced and rippled morphology of 3D graphene provided a path for Au nanoparticles to self-assemble and form rod-like structures on the surface of the 3D graphene. The formation of Au nanorods were showcased through scanning electron microscopy which revealed the evolution of Au nanoparticle into Au islets. Eventually, it formed nanorods possessing lengths of ~ 150 nm and diameters of ~ 30 nm. The X-ray diffractogram displayed appropriate peaks suitable to defect-free and high crystalline graphene with face centered cubic Au. The strong optical interrelation between Au nanorod and 3D graphene was elucidated by Raman spectroscopy analysis. Furthermore, the anchored Au nanorods on 3D graphene nanocomposite enables feasible bio-capturing on the exposed Au surface on defect free graphene. The impedimetric sensing of DNA sequence from TB on 3D graphene/Au nanocomposite revealed a remarkable wide detection linear range from 10 fM to 0.1 ÂµM, displays the capability of detecting femtomolar DNA concentration. Overall, the novel 3D graphene/Au nanocomposite demonstrated here offers high-performance bio-sensing and opens a new avenue for TB detection. Â© 2018 Elsevier B.V.